"Adjustment and liberalization in the Third World / edited by H.W. Singer, Neelamber Hatti and Rameshwar Tandon" - "Singer, H.W. (ed.); Neelambar Hatti (ed.); Rameshwar Tandon " (New Delhi, 1991)
This book deals with world liberalization.
Keywords: Liberalization Developing countries